PERLOCUTIONAL SPEECH ACTIONS IN THE FILM DIALOGUE OF HAFALAN DELISA PRAYER BY SONY GAUKASAK - Erika Nurul Farah; Ellsa Monica Haliza; Muhammad Noor Ahsin; Rosita Rahma; Asep Purwo Yudi Utomo (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2022)
Pragmatics is the study of the relationship between linguistic forms and the users of those forms. Forms of speech acts in speech events include locutionary, illocutionary, and perlocutionary. Perlocutionary acts are speech acts that influence the speech of the speaker and affect and influence the person who is the target of the speech. This study aims to explain the forms of perlocutionary speech acts in the dialogues of the film Memorization of Shalat Delisa by Sony Gaukasak. This research is in the form of a qualitative descriptive study using pragmatic analysis techniques. This research originates from the film Memorization of Prayers Delisa by Sony Gaukasak which is accessed through an application Video.com. The method used in this study is the method of observing and using the technique of observing and noting. The data collection in this study was obtained from the perlocutionary utterances of the characters found in the dialogue film Memorization of the Delisa Prayer by Sony Gaukasak. In this study, 5 types of speech acts were found with 13 perlocutionary speech acts data, namely 4 directive speech acts; commissive speech act 1 piece; expressive speech acts 2 pieces; assertive speech acts 2 pieces; and 4 competitive function speech acts. This research has the benefit of increasing understanding for both students and researchers about the various perlocutionary speech acts in films.